EFFECTIVENESS OF AUTUMN APPLICATION OF HERBICIDES ON WINTER WHEAT - Hnativ П.; Lytvyn О.; Ivaniuk В.; Lahush Н.; Shestak В.; Kotsiuba Б. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
To study effectiveness of autumn application of herbicides on winter wheat, the Department of Plant Technology of Lviv National Environmental University conducted field research in 2019–2021. The soil of the experimental site is dark gray podzolic light loamy with a humus content of 2.6 %. Seven herbicides were studied: Poitner, w.g. (tribenuron-methyl, 750 g/kg); Kvelex, w.g. (galauxifen-methyl, 100 g/kg + florasulam, 100 g/kg + cloquintoset-acid-antidote, 71 g/kg); Grodil Maxi, OD, (amidosulfuron, 100 g/l + iodosulfuron, 25 g/l + mefenpyr-diethyl antidote, 250 g/l); Checker Xtend, w.g. (diflufenican, 240 g/kg + amidosulfuron, 40 g/kg + iodosulfuron, 10 g/kg + mefenpyr-diethyl antidote, 100 g/kg); Stomp 330, e.c. (pendimethalin, 330 g/l); Legato Trio (Trinity), s.c. (pendimethalin, 300 g/l + chlortoluron, 250 g/l + diflufenican, 40 g/l); Marathon, s.c. (pendimethalin, 250 g/l + isoproturon, 125 g/l). The studies have shown that in conditions of sufficient moisture in the Western Forest-Steppe of Ukraine, higher yields were provided by herbicides that controlled both dicotyledonous and monocotyledonous weeds. Yields on herbicide variants that controlled only dicotyledonous weeds were lower due to the high prevalence of Aperaspica-venti. The highest grain yields of winter wheat of the RZT Reform variety were obtained with the autumn application of the herbicides Сhekker Хtend (9.10 t/hа), Legato Trio (8.56 t/ha) and Marathon (8.68 t/ha), which is by 1.28 t/ha, 0.74 t/ha and 0.86 t/ha higher compared to the variant with the application of the herbicide Poitner. Herbicide Marathon provides 100 % technical efficiency on almost all major, most harmful weeds, including the common broom.